Avaliação dos níveis de ansiedade em estudantes universitários - (:unkn) unknown (Universidade Brasil, 2021)
University admission is considered an anxiety generating experience to students due to the educational method transition stage from High School to University. Anxiety is a psychopathology incident in University students in which the symptomatology affects the formal learning construction, generating psychological illness. Scientific studies show a higher incidence of anxiety disorders in the health field students compared to the general population, pointing out the need for IES’ to evaluate the students’ psychological conditions, offering support services. Goal: Assess the anxiety signs and symptoms and its correlation with sociodemographic and lifestyle characteristics in University students. Methods: It is about an analytical and crosssectional study, conducted with 120 University students. The data was collectedthrough the following instruments: Sociodemographic and lifestyle questionnaire, BeckAnxiety Inventory (BAI) and saliva collection and salivary cortisol dosage. The researchwas approved by the Ethics and Research Committee of Universidade Brasil, under the opinion number 3.732.897. Results: A total of 120 students were a part of the study,106 being female and 14 being male students. The average age was 26.4 years old (Median:23.00; Standard deviation: 9.174; Min: 18; Max: 55). Out of the students, 77.5% are single and 76.7% have no kids. For the use of BAI, 16.7% of students had minimal anxiety, 13.3% had mild anxiety, 16.6% moderate anxiety and 53.3% severe anxiety. Regarding the dosage of salivary cortisol in the collected samples, 89.2% of students were within standard limits (under 0.736 µg / dL); 7.8% of students had cortisolvalues above the reference values. Conclusion: The data collected in the studyrevealeda high occurrence of students with signs and symptoms of anxiety disorders.The results reinforce the need for IES’ to include actions to identify students in psychological distress in their practices, concomitant with the adoption of pedagogicalpractices that envision their mental health.
Keywords: Ansiedade; Estudantes; Avaliação da ansiedade; Cortisol salivar; CS